Comparison of Effectiveness and Safety between High-Power Short-Duration Ablation and Conventional Ablation for Atrial Fibrillation: A Systematic Review and Meta-Analysis - Shuyu Jin; Lu Fu; Junrong Jiang; Xingdong Ye; Huiyi Liu; Yanlin Chen; Sijia Pu; Shulin Wu; Yumei Xue (Journal of Interventional Cardiology)
Aim. We aimed to evaluate the effectiveness and safety between high-power short-duration (HPSD) radiofrequency ablation (RFA) and conventional RFA in patients with atrial fibrillation (AF). Methods. Studies comparing HPSD and traditional applications in patients undergoing initial catheter ablation for atrial fibrillation from inception through December 2021 were searched on Pubmed, Medline, Cochrane, and Clinicaltrials.gov. Results. The meta-analysis included seventeen studies with a total of 4934 patients. HPSD group decreased procedure duration (mean difference (MD) −38.28 min, P<0.001), RF duration (MD −20.51 min, P<0.001), fluoroscopy duration (MD −5.19 min, P<0.001), and acute pulmonary vein reconnection (Odds ratio (OR) 0.40, P<0.001), while improving the freedom from atrial arrhythmia at one year (OR 1.48, 95% confidence interval (CI) 1.12–1.94, P=0.005) and rates of first-pass isolation (OR 8.92, P=0.001). Compared with the conventional group, freedom from atrial arrhythmia at one-year follow-up was higher in the HPSD group without the guidance of AI/LSI (OR 1.66, P=0.01) and studies with a power setting of 40–50 W (OR 1.93, P=0.002). Nevertheless, the two groups had similar effectiveness with a power setting of 50 W in the HPSD RFA (OR 1.10, P=0.52). There was no difference in complications between the two groups (P=0.71). Conclusion. HPSD RFA was associated with shorter procedure duration, higher freedom from atrial arrhythmia, and comparable safety compared to conventional RFA.